Inventory of approaches and practices comprising climate-smart agriculture technologies in Southern Africa - Mitti, Joyce; Ngwira, Amos; Magagula, Futhi; Recha, John W.M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The inventory of CSA approaches, practices, and technologies was compiled as an output of the CSA Writeshop that CCARDESA convened in October 2022 under the auspices of the AICCRA and GCCA+ projects with the primary objective of developing the CSA Handbook as well as a training manual for use in SADC region. The CSA Handbook has provided an elaboration of best-bet CSA options that have been categorized along the three pillars of CSA: increased productivity, adaptation, and mitigation. CSA aims to achieve food security and broader development goals under a changing climate and increasing food demand by applying options related to the three pillars. Planning is required to address trade-offs and synergies between these essential pillars. The priority is to achieve more efficient, effective, and equitable food systems that address environmental, social, and economic challenges across productive landscapes. While the CSA handbook has been the primary source of the options in the inventory, only some of the information is excluded from the CSA handbook. Other sources have included other CCARDESA-supported CC projects as well as other relevant CSA literature sources.